Edward Stillingfleet and the 17th Century Episcopacy - Nigel SHARP (E-REA)
The 17th century was a difficult time for bishops in England. Throughout the century, the country was beset with religious and political conflicts and violence, both verbal and physical. This situation was compounded by factions within monarchy, parliament and Church. The Church, in its widest sense, was roughly split between three entities: dissenters, Anglicans and Roman-Catholics. Before the Interregnum, the Episcopacy had been abolished although bishops did not lose their clerical status. Edward Stillingfleet (1635-1699), ordained in 1658 before the Restoration of 1660, believed that Episcopal oversight was the best method of Church jurisdiction. He noted that neither Christ not the Apostles had decreed any specific of Church government. If individual Churches or ministers stayed true to accepted practices and beliefs, there would have been less need for the Episcopacy. After the Glorious Revolution in 1689, Stillingfleet became the Bishop of Worcester. Throughout his career, Stillingfleet continually defended the Episcopacy against attacks by Dissenters who were against Episcopal authority and by Roman-Catholics who felt the bishops had deserted the true Christian faith.